A BRIEF ANALYSIS OF FOREIGN BORROWINGS IN THE UZBEK LANGUAGE (on the materials of newspaper “Khalq suzi”) - Isakova , Nodira (International Journal of Psychosocial Rehabilitation, 2020)
This article deals with analyses of foreign loanwords, their original meanings and translations in the Uzbek language. The borrowing of foreign words increased especially in the years of independence of Uzbekistan due to the reforms almost in all spheres of life. As it’s well known, the mass media is the mirror of culture and language of each nation and state. Surely, the media of Uzbekistan greatly reflects the current life, economical, political and cultural changes in the society. For the first time, the study explored the types of assimilation, its morphological structure and semantic meaning in the Uzbek language, which were introduced not only through the interaction of peoples, but also through the Uzbek media, in particular, newspaper in a short period of time during important reforms.